Biophysical indicators of dental hard tissues, oral liquid, state of microcapillary bed and the degree of inflammation of periodontal tissues in children with diffuse non toxic struma - Rozhko, O. P.; Denga, E. M.; Latash, O. G. (Journal of Education, Health and Sport, 2015)
Rozhko O. P., Denga E. M., Latash O. G. Биофизические показатели твердых тканей зубов, ротовой жидкости, состояния микрокапиллярного русла и степени воспаления тканей пародонта у детей с диффузным нетоксическим зобом = Biophysical indicators of dental hard tissues, oral liquid, state of microcapillary bed and the degree of inflammation of periodontal tissues in children with diffuse non toxic struma. Journal of Education, Health and Sport. 2015;5(2):187-195. ISSN 2391-8306. DOI: 10.5281/zenodo.16037 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%282%29%3A187-195 https://pbn.nauka.gov.pl/works/545759 http://dx.doi.org/10.5281/zenodo.16037 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.10.2014. Revised 18.01.2015. Accepted: 25.02.2015. УДК 616.31–08+616.441–002.63 Биофизические показатели твердых тканей зубов, ротовой жидкости, состояния микрокапиллярного русла и степени воспаления тканей пародонта у детей с диффузным нетоксическим зобом Biophysical indicators of dental hard tissues, oral liquid, state of microcapillary bed and the degree of inflammation of periodontal tissues in children with diffuse non toxic struma О. П. Рожко1, Э. М. Деньга2, О. Г. Латаш2 O. P. Rozhko1, E. M. Denga2, O. G. Latash2 Одесский национальный медицинский университет1, Государственное учреждение «Институт стоматологии Национальной академии медицинских наук Украины»2 Odessa National Medical University1, State Establishment «The Institute of Stomatology of the National academy of medical science of Ukraine»2 Summary Thyroid pathology is an additional risk factor for major dental diseases preventable in children is a topical problem of dentistry. Aim was to study the effectiveness of the integrated prevention of major dental diseases in children with diffuse non toxic struma (DNS). Materials and methods. The study involved 89 children aged 6-7 and 12 years with a diagnosis of DNS. Was evaluated the dynamics of pH stability of of oral liquid, the acid resistance of tooth enamel, its electrical conductivity, the state of the gums and capillary barrier permeability. Results. Conclusions. Children with DNS under the influence of prevention normalization of functional reactions responsible for the maintenance of homeostasis of oral liquid, increasing the acid resistance and the electrical resistance of tooth enamel, normalization the reaction micro capillary bed of gum on the chewing load and reduce gum staining dye solution Schiller-Pisarev, indicating strengthening of its protection barrier and reducing inflammation. Key words: children, diffuse nontoxic struma, prevention of major dental diseases. Реферат Показано, что у детей 6-7 и 12 лет с диффузным нетоксическим зобом под действием разработанного поэтапного комплекса профилактики основных стоматологических заболеваний происходит нормализация функциональных реакций, ответственных за поддержание гомеостаза ротовой жидкости, увеличение кислоторезистентности и электрического сопротивления эмали зубов, нормализация реакции микрокапиллярного русла десны на жевательную нагрузку и уменьшения прокрашиваемости десны для красителя раствора Шиллера-Писарева, что свидетельствует о усилении барьерной ее защиты и уменьшении воспалительного процесса. Ключевые слова: дети, диффузный нетоксический зоб, профилактика основных стоматологических заболеваний. Реферат Показано, що у дітей 6-7 і 12 років з дифузним нетоксичним зобом під дією розробленого поетапного комплексу профілактики основних стоматологічних захворювань відбувається нормалізація функціональних реакцій, відповідальних за підтримку гомеостазу ротової рідини, збільшення кислоторезистентності і електричного опору емалі зубів, нормалізація реакції мікрокапілярного русла ясен на жувальне навантаження і зменшення профарбування ясен для фарбника розчину Шилера-Писарева, що свідчить про посилення бар'єрного її захисту і зменшення запального процесу. Ключові слова: діти, дифузний нетоксичний зоб, профілактика основних стоматологічних захворювань.